2005
DOI: 10.1128/iai.73.8.5252-5255.2005
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of Cryptosporidium hominis and Cryptosporidium parvum Genotype 2 Isolates in Immunosuppressed Mongolian Gerbils

Abstract: One-month-old dexamethasone-immunosuppressed Mongolian gerbils were challenged with 1 oocyst to 2 ؋ 10 5 oocysts from two isolates genotyped as Cryptosporidium hominis and C. parvum (genotype 2), respectively. A similar dose-dependent gut infection was obtained, and the initial genotype maintained for 21 to 22 days. The data suggest that immunosuppressed gerbils provide a reliable rodent model of persistent C. hominis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 41 publications
(50 reference statements)
3
20
0
Order By: Relevance
“…In a retrospective study it was shown that the level of oocysts excretion was higher in Dex-immunosuppressed animals [21,22]. This result is in agreement with Benamrouz et al [14] who showed that in Dex SCID mice inoculated with low doses of oocysts, the excretion of oocysts increased, reaching a mean of oocysts shedding of more than 10,000 oocysts per gram of faeces at forty five days post infection.…”
Section: Discussionsupporting
confidence: 80%
“…In a retrospective study it was shown that the level of oocysts excretion was higher in Dex-immunosuppressed animals [21,22]. This result is in agreement with Benamrouz et al [14] who showed that in Dex SCID mice inoculated with low doses of oocysts, the excretion of oocysts increased, reaching a mean of oocysts shedding of more than 10,000 oocysts per gram of faeces at forty five days post infection.…”
Section: Discussionsupporting
confidence: 80%
“…Interruption of the muscularis mucosae was observed using immunocytochemical staining for alpha 19 smooth muscle actin (Bar=200 m). …”
mentioning
confidence: 99%
“…The MSB data presented above show no difference in sequence diversity between C. hominis and C. parvum and are consistent with the model of adaptative polymorphism, if one considers the possibility that C. parvum and C. hominis share essentially the same host range. This alternative view of Cryptosporidium epidemiology is supported by the sporadic identification of ruminants naturally infected with C. hominis (Ryan et al ., ; Smith et al ., ; Giles et al ., ; Connely et al ., ) and the infection of ruminants and rodents with C. hominis in the laboratory (Giles et al ., ; Akiyoshi et al ., ; Baishanbo et al ., ). The MSB sequence data showing C. hominis sequences in C. parvum isolates are consistent with C. hominis and C. parvum coinfecting animal hosts.…”
Section: Discussionmentioning
confidence: 97%